(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce K^g-filters jointly derived from the class of ideals and the class of generalized complementations in a generalized complemented distributive lattice. We obtain some algebraic properties on the obtained class, and we provide some counter-examples. Mainly we derive some Boolean algebras (distributive lattices) through the class of K^g-filters in a generalized complemented distributive lattice. Finally, we introduce normal K^g-filters in a generalized complemented distributive lattice and then prove that the class of normal K^g-filters is a Boolean algebra.